Peculiarities of morphological indicators of quail spleen (Coturnix japonica Temminck et Schlegel, 1849) when using protein-vitamin mineral supplements - O. F. Dunaievska; I. M. Sokulskiy; L. P. Horalskyi; M. L. Radzikhovskyi; B. V. Gutyj (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
In most countries of the world, poultry farming is one of the main branches of agriculture, which provides the population with high-quality food products. To date, the positive dynamics of the growth of such a branch of industrial poultry farming as quail breeding has been noted. Quails have a complex of excellent economic and productive advantages compared to other agricultural birds – high body temperature, intensive metabolism in the body, small size, precocity, high egg productivity. The question of increasing the productivity of quail breeding, as a branch of precocious animal husbandry, has always occupied the attention of biologists, morphologists, physiologists, geneticists and technologists. This topical problem has various scientific aspects: morphological, histochemical, physiological, genetic, etc. Special attention in the conducted research is required to study the impact of additives on the body of quails, the absence of negative effects and the production of safe products for humans. We chose the spleen as a biomarker, because the spleen is an important peripheral organ of immune protection, sensitive to the action of various factors, whose morphofunctional indicators determine the magnitude and nature of the impact. The purpose of the research was to determine the effect of modern protein-vitamin mineral supplements, which are advertised and offered by producers in the poultry industry to stimulate the growth and development of the bird, on the quail body. In the studies, the features of the microscopic structure and morphometry of the spleen of control and experimental animals were used as sensitive characteristics of the action of additives. The proposed methods are aimed at researching the impact of protein-vitamin mineral supplements on the relevant industry. So, for 21 days, mineral supplements “Multilife”, “Missy” and “Standard Agro” were added to the main ration of quails. Using macrometric methods, the body weight of quails, the weight of the spleen (absolute and relative) were determined. For histological studies, pieces of the spleen were fixed in a 10 % formalin solution, and after embedding in paraffin, histological sections were prepared from it, which after deparaffinization were stained with hematoxylin and eosin, according to the methods of Brachet and Van Gieson. For electron microscopic examination, the spleen was immediately fixed with a 2.5 % solution of glutaraldehyde in a phosphate buffer with additional fixation in a 1 % solution of osmium tetroxide according to Caulfield. For the first time, the ultrastructural organization of the spleen of Japanese quail was investigated after feeding protein-vitamin mineral supplements, which may indicate the absence of their negative impact on the structural and functional state of the spleen. Important morphological structural indicators of the morphofunctional state of the spleen were determined: the relative area of the white pulp, red pulp, lymphoid nodules, periarterial lymphoid sheaths, and the contractile apparatus. According to the analysis of the morphological results obtained by us, it was investigated that the microscopic structure of the quail spleen is characterized by the presence of a support-contractile apparatus with a relative area of 4.58 ± 0.76 % and single radial trabeculae. The parenchyma is formed by white and red pulp without clear boundaries. Lymphoid nodules without bright centers, periarterial lymphoid sheaths, and ellipsoids were identified as part of the white pulp. The ultrastructural organization of the spleen of quails had peculiarities: the nuclei of leukocytes contain large nucleoli, the endotheliocytes of the central artery of the lymphoid follicle perform a phagocytic function by accumulating autophagosomes in their cytoplasm. The macroscopic, microscopic and ultramicroscopic structure of quails that were added to the main diet with the listed additives did not undergo any changes. As a result, the following supplements led to an increase in the body weight of quails: by 5.78 % when using the Multilife supplement, by 12.51 % when using the Missy supplement, and by 8.12 % when using the Standard Agro supplement, and the weight of the spleen on 7.17 %, 16.04 % and 10.54 %, respectively. The conducted studies showed that the relative weight of the organ practically did not change. At the same time, there is a trend towards an increase in the relative area of the white pulp and the supporting-contractile apparatus. Taking into account the obtained data, it can be concluded that our research confirms the feasibility of using modern protein-vitamin mineral supplements in poultry farming to stimulate the growth and development of poultry. Especially valuable is the absence of a negative effect on the morphofunctional indicators of the spleen, which was used as a biomarker in research.